2014
DOI: 10.1103/physrevb.89.134502
|View full text |Cite
|
Sign up to set email alerts
|

Sudden reversal in the pressure dependence ofTcin the iron-based superconductor CsFe2As2: A possible link between inelastic scattering and pairing symme

Abstract: We report a sudden reversal in the pressure dependence of T c in the iron-based superconductor CsFe 2 As 2 , similar to that discovered recently in KFe 2 As 2 [Tafti et al., Nat. Phys. 9, 349 (2013)]. As in KFe 2 As 2 , we observe no change in the Hall coefficient at T → 0, again ruling out a Lifshitz transition across the critical pressure P c . We interpret the T c reversal in the two materials as a phase transition from one pairing state to another, tuned by pressure, and we investigate which parameters con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 20 publications
7
57
0
Order By: Relevance
“…These ideas gained experimental relevance with our recent discovery of a V-shaped T -P phase diagram in KFe 2 As 2 and CsFe 2 As 2 , where T c decreases initially as a function of pressure, then at a critical pressure P c , it suddenly changes direction and increases. 5,6 Our results on KFe 2 As 2 have been reproduced by other groups. [7][8][9] We interpreted the transition at P c as a change of pairing state, possibly from d to s ± , where the decreasing T c of the former meets the growing T c of the latter at P c , resulting in a V-shaped phase diagram.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…These ideas gained experimental relevance with our recent discovery of a V-shaped T -P phase diagram in KFe 2 As 2 and CsFe 2 As 2 , where T c decreases initially as a function of pressure, then at a critical pressure P c , it suddenly changes direction and increases. 5,6 Our results on KFe 2 As 2 have been reproduced by other groups. [7][8][9] We interpreted the transition at P c as a change of pairing state, possibly from d to s ± , where the decreasing T c of the former meets the growing T c of the latter at P c , resulting in a V-shaped phase diagram.…”
Section: Introductionsupporting
confidence: 79%
“…a Lifshitz transition. 5,6 We concluded that the phase transition at P c is not triggered by some change in the Fermi surface, and is instead associated with a change in the superconducting state itself. This was confirmed by quantum oscillation measurements on KFe 2 As 2 under pressure, which found a smooth evolution of the oscillation frequencies and cyclotron masses across P c .…”
Section: B Pressure Dependence Of Rhmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance the dependence of T c on pressure for MgB 2 indicated a mediating electron-phonon coupling [35]. Recently, in Bi 2 Se 3 an anomalously saturating p dependence of T c (for p > 30.0 GPa) suggested the presence of an unconventional pressure-induced superconducting pairing state in this topological insulator [36] and pressure-induced reversal of the dependence of T c on pressure in KFe 2 As 2 indicated a pairing state transition [37]. Investigations have mainly focussed on the study of T c (p) [38].…”
Section: Discussion Pressure Dependence Of Superconducting Parametersmentioning
confidence: 99%